EXTENDING DYNAMICS 365 CUSTOMER ENGAGEMENT APPS WITH LOW CODE : create tailor-made dynamics 365 ... ce apps using powerful low-code capabilities of power platform - FERNANDEZ, NICOLAS ANDRES (PACKT Publishing Limited, 2023)
Customize your Dynamics 365 customer engagement apps to increase business productivity and customer value at scale using a low-code approach Key Features Leverage Power Apps and customize Dynamics 365 CE apps to implement advanced business case scenarios Create automation with Power Automate to empower Dynamics 365 CE users to increase their productivity Easily build bots using Power Virtual Agents for both internal and external use cases Book Description Extending Dynamics 365 Customer Engagement Apps with Low Code helps you gain a comprehensive, practical understanding of how a no-code/low-code project approach works for Dynamics 365 (D365) Customer Engagement (CE). This book covers the most relevant native capabilities for configuration, along with real-world scenarios to showcase the magic of extending D365 CE apps with Power Platform. The book starts by identifying different scenarios and use cases to extend D365 CE apps with a low-code approach. You'll learn about the different capabilities of Dataverse and Power Apps used to extend native applications. Next, you'll discover how to leverage Power Apps, both Canvas apps and model-driven apps, and Power Pages, to build apps and portals around D365 CE processes. You'll also explore Power Automate's capabilities to create or modify business processes, as well as incorporate new processes and automation. As you advance, you'll also discover how Power Virtual Agents can be implemented in D365 CE apps. The book concludes by teaching you to integrate Power BI natively with customer engagement, thus facilitating the construction of advanced reports and dashboards. By the end of this book, you'll have gained hands-on expertise in customizing CE apps with Power Platform to deliver more scalable and maintainable solutions. What you will learn Leverage the capabilities of Dataverse and Power Apps to extend Dynamics 365 CE native applications Create Canvas and model-driven apps on top of Dynamics 365 CE applications Integrate AI Builder capabilities with Dynamics 365 CE for advanced solutions Create automation with business process flow, cloud flows, and classic workflows Deploy a chatbot and integrate it with Dynamics 365 CE processes Embed Power BI dashboards and reports in Dynamics 365 CE apps Who this book is for This book is for Dynamics 365 developers, solutions architects, technical functional consultants, and pre-sales architects working on Dynamics 365 customer engagement who want to customize and extend their customer engagement apps with the power of low-code/no-code technology, and gain practical experience in using Power Platform components to deliver scalable, maintainable, and intelligent solutions to their clients. Working knowledge of Dynamics 365 and basic knowledge of low-code/no-code technology will help you get the most out of this book.